Comparative Morphology and Ultrastructure of Antennal Sensilla in Dendrolimus superans (Lepidoptera: Lasiocampidae) and Lymantria dispar (Lepidoptera: Lymantriidae) - Qi Wang; Longzheng Wang; Qing Wang; Shanchun Yan (Insects)
Dendrolimus superans (Lepidoptera: Lasiocampidae) and Lymantria dispar (Lepidoptera: Lymantriidae) are two important forest defoliators in northeast China, with the former being a specialist on Larix spp. and the latter being a generalist feeding on >500 species of plants. The morphology and ultrastructure of antennal sensilla of both male and female D. superans and L. dispar were examined using scanning electron microscopy (SEM). In both sexes of D. superans, the following five types of antennal sensilla were found: sensilla trichoidea, s. chaetica, s. coeloconica, s. gemmiformia, and s. basiconica. In males of L. dispar, six types of antennal sensilla: sensilla trichoidea, s. chaetica, s. coeloconica, s. basiconica, s. styloconica, and s. auricillica, were identified. In addition to the six types found in males, a seventh type of sensilla, s. squamiform, was only detected on L. dispar female antennae. For s. chaetica of D. superans, a unique ultrastructure of sub-branches that have one branch, two branches, and three branches was observed on their tips, which has not yet been reported on other insects. s. styloconica, s. auricillica, and s. squamiform, not found in the specialist D. superans, may be related to the euryphagy of L. dispar. Potential functionalities of these sensilla were discussed with reference to moth feeding habits, and their morphology, distribution, and ultrastructures on both species.